Is There a Threshold Oral Glucose Tolerance Test Value for Predicting Adverse Pregnancy Outcome? - Stuebe, Alison M.; Landon, Mark B.; Lai, Yinglei; Klebanoff, Mark; Ramin, Susan M.; Wapner, Ronald J.; Varner, Michael W.; Rouse, Dwight J.; Sciscione, Anthony; Catalano, Patrick; Saade, George; Sorokin, Yoram; Peaceman, Alan M.; for the Eunice Kennedy Shriver National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network, Bethesda, MD (American Journal of Perinatology, 2015)
Objective This study aims to determine whether there is a threshold 3-hour oral glucose tolerance test (OGTT) value associated with accelerated risk of adverse pregnancy outcomes.Study Design In a secondary analysis of a cohort of women with untreated mild gestational glucose intolerance, we used generalized additive models with smoothing splines to explore nonlinear associations between each of the 3-hour OGTT values (fasting, 1-hour, 2-hour, and 3-hour) and adverse pregnancy outcomes, including the study's composite outcome (perinatal mortality, hypoglycemia, hyperbilirubinemia, neonatal hyperinsulinemia, and/or birth trauma), large for gestational age birth weight, small for gestational age birth weight, shoulder dystocia, neonatal hypoglycemia, gestational hypertension (gHTN), and preeclampsia.Results Among the 1,360 eligible women, each timed OGTT value was linearly associated with increased odds of composite adverse outcome. We found evidence of a departure from linearity only for the association between fasting glucose and gHTN/preeclampsia, with a stronger association for values of 85 to 94 mg/dL (p = 0.03). We found no evidence of departure from linearity for any other OGTT values and measured outcomes (all chi-square test p-values ≥ 0.05).Conclusion In a population of untreated women with mild gestational glucose intolerance and fasting OGTT < 95 mg/dL, we found an increasing risk of gHTN with a fasting glucose between 85 and 94 mg/dL.
Keywords: gestational diabetes; glucose; preeclampsia; macrosomia